2022
DOI: 10.3389/fpsyt.2022.994376
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between perceived social support with anxiety, depression, and insomnia among Chinese college students during the COVID-19 pandemic: The mediating role of self-control

Abstract: ObjectWe aimed to investigate the associations between perceived social support and anxiety, depression, and sleep disturbance via self-control among Chinese college students during the COVID-19 pandemic.Materials and methodsThe Perceived Social Support Scale, Self-control Scale, Self-rating Anxiety Scale, Self-rating Depression Scale, and Insomnia Severity Index Scale were used to survey 1,997 college students during the COVID-19 pandemic, who submitted valid questionnaires (Mage = 19.93, SDage = 1.47, Range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Though our data are in line with many previous studies, it is hard to establish a causal relationship between pandemic context and mental health disorders in a cross-sectional study. The study might be improved in the future by increasing the correlation analysis between mental health and other factors such as perceived social support, living environment (urban or rural area), physical activity, sedentary time, and dietary behaviors ( Ivbijaro et al, 2021 ; Shibata et al, 2021 ; Rahim et al, 2022 ; Silva et al, 2022 ; Zhao et al, 2022 ). Furthermore, mood disturbance has been reported to be associated with inflammatory processes ( Beurel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though our data are in line with many previous studies, it is hard to establish a causal relationship between pandemic context and mental health disorders in a cross-sectional study. The study might be improved in the future by increasing the correlation analysis between mental health and other factors such as perceived social support, living environment (urban or rural area), physical activity, sedentary time, and dietary behaviors ( Ivbijaro et al, 2021 ; Shibata et al, 2021 ; Rahim et al, 2022 ; Silva et al, 2022 ; Zhao et al, 2022 ). Furthermore, mood disturbance has been reported to be associated with inflammatory processes ( Beurel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A 7-level score was used, and the higher the score, the higher the degree of social support felt by the individual. This scale has been widely used in the study of Chinese population and has been proven to have good reliability and validity [ 47 , 48 ]. The Cronbach’s α coefficient of the scale in this study was 0.962.…”
Section: Methodsmentioning
confidence: 99%
“…Third, critically, this study focused primarily on the presence of meaning and perceived social support, overlooking the potential impact of other factors. For instance, recent research has demonstrated that future self-continuity has a direct influence on individuals' self-control (Zhang & Gao, 2023), which in turn is associated with depression (Zhao et al, 2022). Thus, self-control may serve as a potential mediating mechanism through which future self-continuity influences depression.…”
Section: Implications and Limitationsmentioning
confidence: 99%